Impact of obesity, genetic predisposition and comorbidities on pregnancy-related hypertension - Partiwi, Nur; Hafid, Rachmi Nurul Hidayat (Advances in Healthcare Research, 2025)
Purpose: This study aims to explore the impact of obesity, genetic predisposition, and comorbidities on pregnancy-related hypertension. Given the rising prevalence of maternal obesity and associated metabolic disorders, understanding how these factors contribute to hypertensive complications during pregnancy is crucial for developing effective prevention and management strategies. The study also examines the role of genetic susceptibility and pre-existing medical conditions in exacerbating hypertensive risks, emphasizing the need for a holistic approach in maternal healthcare. Research Design and Methodology: This study employs a systematic literature review (SLR) to synthesize findings from existing research on the relationship between obesity, genetic factors, and comorbidities in relation to pregnancy-related hypertension. Relevant peer-reviewed articles from Elsevier, Emerald, Wiley, and Springer published after 2018 were analyzed to identify key trends, mechanisms, and clinical implications. The review integrates evidence from obstetrics, endocrinology, genetics, and public health to provide a comprehensive understanding of the topic. Findings and Discussion: The study reveals that obesity significantly contributes to hypertensive disorders in pregnancy through mechanisms such as endothelial dysfunction, chronic inflammation, insulin resistance, and RAAS activation. Genetic predisposition, particularly polymorphisms in RAAS-related genes (AGT, ACE, AGTR1) and endothelial function genes (eNOS, VEGF), is strongly associated with an increased risk of hypertension. Additionally, pre-existing conditions such as diabetes mellitus, chronic hypertension, kidney disease, and autoimmune disorders further aggravate hypertensive complications. Implications: The findings underscore the importance of early screening programs, personalized treatment approaches, and interdisciplinary prenatal care. Healthcare policymakers should develop standardized guidelines for managing hypertensive pregnancies complicated by obesity and comorbidities. The study highlights the importance of lifestyle interventions, genetic screening, and pharmacological advancements in reducing pregnancy-related hypertension risks and improving maternal-fetal health outcomes.